Palm oil-based polyester binder for making fiberboards / Wong Yew Chuan - Wong, Yew Chuan (2010)

(untitled)
Palm kernel oil was used as a raw material for the synthesis of polyester polyol.The palm oil based polyester polyol was synthesized using glycerol, phthalic anhydride and fumaric acid. Palm oil based polyester polyol combines with methylene diphenyl diisocyanate (MDI) to form the polyurethane binder. The fibers are derived from empty fruit bunch (EFB) of the palm tree and have the acceptable mechanical properties. In this project, palm fibers were converted into palm fiberboards by using polyurethane (PU) binder under specified pressure and temperature. The binder to fiber ratio was varied from 10% to 30 % by dried weight of the palm fiber. The curing temperature was set from 60°C to 100°C and curing pressure was between 3 MPa to 7 MPa. The curing time was from 5 to 25 minutes. The density, tensile strength, modulus of elasticity, flexural strength, impact strength, water absorption and swelling of fiberboards were determined. Increase of the PU binder content and the NCO/OH ratio would significantly improve the mechanical properties of the fiberboards. The fiberboards made from fine fiber had better mechanical properties than those made from palm fiber mat, which comprise mainly of longer fibers.